2012
DOI: 10.1039/c2jm32649c
|View full text |Cite
|
Sign up to set email alerts
|

Graphene wrapped LiFePO4/C composites as cathode materials for Li-ion batteries with enhanced rate capability

Abstract: To reduce the reaction time, electrical energy consumption, and cost, LiFePO 4 /C/graphene has been synthesized by a rapid, one-pot, microwave-assisted hydrothermal method within 15 min at a temperature of 200 C, followed by sintering at 600 C for 2 h under a H 2 /Ar (5 : 95, v/v) atmosphere.The microstructure and morphology of the LiFePO 4 /C/graphene products were characterized by means of X-ray diffraction, Raman spectroscopy, field emission scanning electron microscopy, and transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(132 citation statements)
references
References 35 publications
6
116
2
2
Order By: Relevance
“…The EG-wrapped cLFP cathodes provide the capacity from 187 to 208 mAh g À 1 , depending on the weight percentage of EG (from 0.8 to 2 wt%). These values are higher than the reported values of 120-160 mAh g À 1 for commercially available or synthetic LFP materials in research laboratories 16,17,21,22 . Surprisingly, these values are even in excess of the theoretical value of 170 mAh g À 1 for LFP.…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…The EG-wrapped cLFP cathodes provide the capacity from 187 to 208 mAh g À 1 , depending on the weight percentage of EG (from 0.8 to 2 wt%). These values are higher than the reported values of 120-160 mAh g À 1 for commercially available or synthetic LFP materials in research laboratories 16,17,21,22 . Surprisingly, these values are even in excess of the theoretical value of 170 mAh g À 1 for LFP.…”
Section: Resultscontrasting
confidence: 65%
“…Alternatively, significant effort has been devoted to coating the LFP surfaces with electrically conductive materials, such as amorphous carbon and conducting polymers to ARTICLE enhance the electrical conductivity of LFP surfaces [27][28][29][30][31][32] . Recent studies have adopted rGO or GO to cover the LFP surfaces [16][17][18][19] . However, studies so far have only shown certain improvements in the rate capability but no report has exceeded the theoretical limit of the capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite with a low content of graphene exhibited a high initial discharge capacity of 163. performance compared to the conventional graphene/LiFePO 4 composite and bare LiFePO 4 . The as-obtained sample delivered 73 mAh g −1 of discharge capacity at 25 C. Shi and co-workers [101] described an advanced microwave-assisted hydrothermal route for preparation of a highly ordered LiFePO 4 /C/graphene nano-composite. LiFePO 4 /C nanoparticles were embedded in the conductive and interconnected graphene networks, and exhibited a discharge capacity of 88 mAh g −1 at 10 C.…”
Section: Preparation Of Compositesmentioning
confidence: 99%
“…Utilizing graphene in LiFePO4 composites resulted in achieving near theoretical specific capacity (i.e., 170 mAh/g), exceptional rate capability and improved the cycle life due to intimate contact between non-aqueous electrolyte and the LiFePO4 active materials as well as enhanced the charge and mass transfer [110,111]. The schematic of the graphene wrapped LiFePO4 particles are shown in Figure 11 [111]. Hu et al reported that electrochemically exfoliated graphene wrapped commercial LiFePO4 particles can deliver 208 mAh/g capacity which is more than the theoretical capacity of LiFePO4.…”
Section: Olivine Limpo 4 (M = Fe Co Mn and Their Mixtures)mentioning
confidence: 99%